The scope of childhood cancer in South Africa: A response to 'Childhood cancers in a section of the South African private health sector - Analysis of medicines claims data' - Jaques van Heerden; Mariana Kruger (AOSIS, 2021)
Childhood cancer is an under resourced medical field that is emerging as a great healthcare concern in low- and middle-income countries such as South Africa. Therefore, reporting data in this field that may inform policymakers should be representative of the subject matter. This article aims to discuss why medicines claims as an indicator for incidence, as per an article published in 2020, is not representative of childhood malignancies in the South African setting. Literature to support the commentary were sourced using Pubmed, Google scholar, and data presented by members of the South African Children's Cancer Study Group (SACCSG). Private medical aid coverage in South Africa between 2002 and 2018 varied between 15.5% and 18.2%. Of these, 9.5% were children under 18 years and 3.5% were under the age of six. Only 13.5% of children were treated in private paediatric oncology units during 2015. The limitations in the study were the variable medical aid coverage, the disproportionate age representation, and lack of reliable indicators for measurement and calculation of incidence. Utilising one medicines claims database to evaluate the incidence of childhood cancer in South Africa is not representative and cannot inform policy. Contribution: This article highlights the importance of accurate registration of childhood cancer diagnoses, especially when data and conclusions based on these results inform policy. The study highlights the limitations of extrapolating general conclusions based on data representing only a small sector of the childhood cancer landscape in South Africa.